2010
DOI: 10.1063/1.3340930
|View full text |Cite
|
Sign up to set email alerts
|

Correlated d ferromagnetism and photoluminescence in undoped ZnO nanowires

Abstract: We report the correlated d0 ferromagnetism and photoluminescence in undoped single-crystalline ZnO nanowires synthesized by using a vapor transport method. We systematically tune the oxygen deficiency in the ZnO nanowires from 4% to 20% by adjusting the growth conditions, i.e., selecting different catalyst (Au or Ag) and varying the growth temperature. Our study suggests that oxygen vacancies induce characteristic photoluminescence and significantly boost the room-temperature ferromagnetism. Such undoped ZnO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(122 citation statements)
references
References 29 publications
5
115
2
Order By: Relevance
“…The manipulation of impurities by the consequences of structural and chemical inhomogeneity in nanostructures is often advantageous to induce magnetism. [9][10][11][12] Adding to these existing literatures, room temperature ferromagnetism has been reported in undoped GaN nanoparticles and this intrinsic behaviour was linked to the defects at the surface of the nanoparticles. 13 The origin of magnetism in wurtzite GaN has been ascribed to the presence of Ga vacancy (V Ga ), N vacancy (V N ) and impurities such as oxygen in several theoretical reports.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The manipulation of impurities by the consequences of structural and chemical inhomogeneity in nanostructures is often advantageous to induce magnetism. [9][10][11][12] Adding to these existing literatures, room temperature ferromagnetism has been reported in undoped GaN nanoparticles and this intrinsic behaviour was linked to the defects at the surface of the nanoparticles. 13 The origin of magnetism in wurtzite GaN has been ascribed to the presence of Ga vacancy (V Ga ), N vacancy (V N ) and impurities such as oxygen in several theoretical reports.…”
mentioning
confidence: 99%
“…The emergence of FM in undoped oxides is often described as d o ferromagnetism. 11,12 Already there has been a strong consensus arrived that the magnetism in wide-band-gap oxides is often closely linked to the existence of structural impurities like vacancies and point defects. 9,12 Thus, the defect ferromagnetism has received a considerable boost by the metal oxide semiconductors invoking that the underlying physics is universal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 Very weak magnetization was observed in undoped ZTO nanowires, in agreement with previous reports of undoped oxides ZnO and In 2 O 3 , where it was attributed to intrinsic defects. [39][40][41][42] Mn doping clearly increased the magnetism in ZTO nanowires. The saturation magnetization monotonously increased with increasing Mn content: The saturated room temperature magnetic moment of ZTO:Mn-2 was twice that of ZTO:Mn-1, which indicated that magnetic properties correlated closely with Mn content.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of defects on the observed magnetic properties of the ZnO nanostructures are often preliminarily characterized through PL. Usually the observed RTFM in ZnO nanostructures can be connected with defects as evidenced from the visible emission in PL [55,97,99]. In particular, the green emission around 520 nm has been attributed to singly occupied oxygen vacancy V + o , the yellow emission around 580 nm to doubly charged oxygen vacancy V 2+ o , and the orange-red emission to interstitial oxygen O i on the ZnO surface [91,92,98].…”
Section: Rtfm In Undoped Zno Nanostructuresmentioning
confidence: 99%